Magical Medicine The Folkloric Component of Medicine in the Folk Belief, Custom, and Ritual of the Peoples of Europe and America. - Hand, Wayland D. (University of California Press, 2021)
""Distilling baby's first tear into the eye of a blind man to make him see""; ""Plucking herbs upward for emetics and downward for purgatives""; ""Stroking one's goiter with a dead man's hand to make the growth shrivel away""--these are not beliefs and customs found among primitive peoples in remote parts of the world but are examples of hundreds of items of magical medicine found in Professor Hand's remarkable collection of essays dealing with this neglected.